2021
DOI: 10.1136/bmjopen-2020-043869
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the current state of Nigeria’s emergency care system among participants of an emergency medicine symposium: a qualitative appraisal

Abstract: IntroductionEmergency care systems provide timely and relevant care to the acutely ill and injured. Published commentaries have characterised deficiencies in the Nigerian emergency care system and offered potential solutions but have not included the perspectives of the Nigerian public. A more inclusive approach that includes feedback from the public may help improve the Nigerian emergency care system through better understanding of the needs, values and expectations of the community.MethodsParticipants of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…The role of EMS is spread across numerous public and private organizations resulting in lack of resources integration and protocols standardization implying that EMS as a whole is fragmented and are underfunded or inconsistently funded which further reduces the capacity as well as quality of EMS. 4 Similar characteristics of EMS are also evident in countries like Nepal, 5,6 Nigeria, 7 Vietnam, 8 and South Asian 9 and African 10 nations. Sheu and Pan 11 have shown that a centralized emergency supply network in response to a large scale disaster is efficient than a de-centralized system in terms of cost as well as response time.…”
Section: Introductionmentioning
confidence: 79%
“…The role of EMS is spread across numerous public and private organizations resulting in lack of resources integration and protocols standardization implying that EMS as a whole is fragmented and are underfunded or inconsistently funded which further reduces the capacity as well as quality of EMS. 4 Similar characteristics of EMS are also evident in countries like Nepal, 5,6 Nigeria, 7 Vietnam, 8 and South Asian 9 and African 10 nations. Sheu and Pan 11 have shown that a centralized emergency supply network in response to a large scale disaster is efficient than a de-centralized system in terms of cost as well as response time.…”
Section: Introductionmentioning
confidence: 79%
“…Some of these practices, such as the provision of care from untrained family members and bystanders who do not recognize an emergency, may delay care. Others, such as applying direct fire and flame to the feet of a convulsing child to rid them of the evil spirits that caused the seizure, are harmful [18] . Other challenges inhibit the provision of care by bystanders.…”
Section: Discussionmentioning
confidence: 99%
“…The provision of EMS in Nigeria is still nascent after different failed attempts by national and state governments at establishing a comprehensive emergency system in the country. This has resulted in inadequate and often delayed medical care for individuals with medical emergencies [ 16 18 ]. Challenges of EMS include a lack of infrastructure, limited resources, and inadequate training [ 16 ].…”
Section: Introductionmentioning
confidence: 99%